Historia e direito: a literatura de cordel como instrumento para (in)formação da cidadania - Santana, Frederico Heberth Carvalho de (My University, 2025)
This work explores the (in)formation of citizenship through literatura de cordel, recognizing it as a pedagogical tool that transcends educational and social barriers. The study highlights the ability of cordel to serve as a resource for reading and interaction, accessible to both literate and non-literate individuals, thereby expanding the reach of civic education. By using interdisciplinarity as a central axis, the research investigates how this popular literary form can be integrated into teaching, fostering the development of cognitive, reading, and social criticism skills among students. The research also examines the intersection between Literatura de Cordel and Law, with an emphasis on notarial and registral activities, traditionally seen as tools for the consolidation of citizenship. The discussion highlights how cordel booklets not only record historical experiences but also promote awareness of citizens' rights and duties, contributing to the formation of a more informed and participative society. As one of the practical results of this study, the development of a specific cordel on History, citizenship and notarial and registry activities is proposed, which was prepared and made available as a final educational product, aiming to be a didactic resource for educators and an accessible source of knowledge for communities in different regions of Brazil. By integrating the tradition of cordel and its historical approach with legal practice, the work offers new perspectives for the teaching of citizenship, making it more inclusive and culturally relevant. [resumo fornecido pelo autor]
Este trabalho explora a (in)formação da cidadania através da literatura de cordel, reconhecendo-a como uma ferramenta pedagógica que ultrapassa barreiras educacionais e sociais. O estudo destaca a capacidade do cordel de atuar como um recurso de leitura e interação, acessível a pessoas alfabetizadas e não alfabetizadas, ampliando o alcance da educação cidadã. Ao utilizar a interdisciplinaridade como eixo central, a pesquisa investiga como essa forma literária popular pode ser integrada ao ensino, fomentando o desenvolvimento de habilidades cognitivas, de leitura e de crítica social entre os educandos. A pesquisa também examina a ligação entre a literatura de cordel e o Direito, com ênfase nas atividades notariais e registrais, tradicionalmente vistas como ferramentas de consolidação da cidadania. A discussão destaca como os folhetos de cordel registram experiências históricas e promovem a conscientização sobre os direitos e deveres dos cidadãos, contribuindo para a formação de uma sociedade mais informada e participativa. Como um dos resultados práticos deste estudo, é proposto o desenvolvimento de um cordel específico sobre História, Cidadania e atividades notariais e registrais, que foi elaborado e disponibilizado como um produto educacional final, visando ser um recurso didático para educadores e uma fonte de conhecimento acessível para comunidades em diversas regiões do Brasil. Ao integrar a tradição do cordel e sua abordagem histórica com a prática jurídica, o trabalho oferece novas perspectivas para o ensino da cidadania, tornando-o mais inclusivo e culturalmente relevante. [resumo fornecido pelo autor]
Keywords: História - Estudo e ensino; Literatura de cordel; Direito; Cidadania; History - Study and teaching; Chapbooks; Law; Citizenship